2023
DOI: 10.1055/s-0043-1764231
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Patient Characteristics, Risk Factors, and Symptomatology in Older Adults with Pulmonary Embolism: Findings from the SERIOUS-PE Study

Abstract: Sex-specific factors are implicated in pulmonary embolism (PE) presentation in young patients, as indicated by increased risk in pregnancy. Whether sex differences exist in PE presentation, comorbidities, and symptomatology in older adults, the age group in which most PEs occur, remains unknown. We identified older adults (aged ≥65 years) with PE in a large international PE registry replete with information about relevant clinical characteristics (RIETE registry, 2001–2021). To provide national data from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…An analysis of the Registro Informatizado Enfermedad Tromboembolica(RIETE) and Medicare databases revealed that gender potentially has an influence on the risk factors associated with PE, as women afflicted with PE exhibited a higher propensity for immobility or hormonal treatment in contrast to their male counterparts. Conversely, the prevalence of cancer and cardiovascular diseases was observed to be greater among men [ 8 ]. This aligns with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the Registro Informatizado Enfermedad Tromboembolica(RIETE) and Medicare databases revealed that gender potentially has an influence on the risk factors associated with PE, as women afflicted with PE exhibited a higher propensity for immobility or hormonal treatment in contrast to their male counterparts. Conversely, the prevalence of cancer and cardiovascular diseases was observed to be greater among men [ 8 ]. This aligns with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research highlights a heightened incidence of PE in females compared to males [5][6][7][8]. This gender discrepancy may be attributed to anatomical and hormonal factors, although further investigation is needed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, present findings strengthen previous data from large series that underline the need to design prospective studies to better investigate in women the risk of rare and life-threatening thrombosis, as CVT or PE. 12 24 25…”
Section: Discussionmentioning
confidence: 99%
“…In addition, present findings strengthen previous data from large series that underline the need to design prospective studies to better investigate in women the risk of rare and life-threatening thrombosis, as CVT or PE. 12,24,25 One limitation of this study is its observational nature that does not allow to control a priori for possible confounders as it happens in RCTs. However, START registry is not designed to answer questions regarding the relative efficacy and safety of different modalities of therapy.…”
Section: Strengthen and Limitationsmentioning
confidence: 99%
“…Bikdeli and colleagues have now investigated how elderly (≥65 years) females versus males differ regarding risk factors and symptoms of pulmonary embolism. 8 They used data from the large Registro Informatizado de la Enfermedad Trombo-Embólica (RIETE) registry and the U.S. Medicare database. In both datasets, the proportion of females was higher than that of males in patients with pulmonary embolism.…”
mentioning
confidence: 99%